Realization of Structural Colors via Capped Cu-based F-P Cavity Structure - Rahman, M. A.; Kim, Yun Hee; Cho, So-Hye; Lee, Seung Yong; Byun, Ji Young (Optical Society of America, 2021)
Structural colors with tunable properties have several applications in the beautification of mobile devices, surface decoration, art and color filters. Herein, we propose an asymmetric F-P cavity design to systematically tune structural colors by changing the thickness of the top metal and intermediate insulator. In this study, Cu and Si3N4 were chosen as the top metal and intermediate insulator layers, respectively, various reflection colors being realized on the Cu surface. Various capping layers-that is, SiO2, polymethyl methacrylate (PMMA), and a commercially available clear coat named ProtectaClear-were used to protect the Cu surface from scratching and oxidation. PMMA coatings can protect Cu from corrosive environments without degradation of the color quality. The colors can be tuned by controlling the thickness of either the metal or intermediate insulator layers, and vivid structural colors-including orange, bright orange, red, purple, violet, light blue, green-yellow, and yellow-green-can be printed. The colors obtained can be attributed to thin-film interference. (C) 2021 Optical Society of America under the terms of the OSA Open Access Publishing Agreement